A Study to Assess the Level of Knowledge of Cannabis Use Disorder among Adolescents - Tanushree Mitra; Punita A Sharma; Radhika Das; Sindhu Gopal (Indian Journal of Psychiatric Nursing)
Background: Adolescents are exploring in nature. Their natural tendency to seek pleasure through experiments and exploration makes them more vulnerable. The problem of cannabis use emerged in a great way as it was thought of harmless and recreational drugs for a long time. The present study explored the knowledge level of adolescents regarding cannabis use disorder which was not explored much. Method: A Cross-sectional Descriptive study, conducted among school going urban adolescents in selected schools of western Maharashtra during October -December 2018. The study was conducted among 259 adolescents. The knowledge regarding cannabis use disorder was assessed by self- administered questionnaire of 20 items along with the relevant socio-demographic and substance use related data. Results: The study revealed that most of the samples (82.63%) had average level of knowledge, few of the samples (17.37%) had poor knowledge and nil had good level of knowledge of cannabis use disorder. There was statistically significant association between the knowledge score and the sex(0.013), level of education (0.003) and the monthly family income(0.019). Conclusion: Most of the adolescents either had average or poor knowledge of cannabis use disorder. A module needs to be developed and disseminated among adolescents to increase their knowledge level and awareness. Involvement of parents and school teachers were suggested.